A two-person collaborative repositioning approach for high peritoneal dialysis catheter migration: case reports and literature review - F. Zhuangyan Yao; S. Yanqing Li; T. Liping Zhai (BMC Nephrology)
Abstract Background Peritoneal dialysis catheter migration, a common complication in patients undergoing peritoneal dialysis, often leads to poor dialysate drainage, infection, and abdominal pain. Timely and effective treatment of catheter migration is essential to ensure uninterrupted dialysis. Case presentation This study presents three cases of peritoneal dialysis (PD) catheter displacement in patients with end-stage renal disease (ESRD), involving three elderly individuals aged 80, 81, and 76 years. All instances of catheter displacement were primarily localized to the upper abdominal region. Following unsuccessful attempts with traditional repositioning methods (such as positional adjustments, ambulation, and saline infusion), a two-person collaborative repositioning technique was employed, combining external manual pressure with rapid saline injection. Consequently, all catheters were successfully repositioned to the pelvic area and remained stable throughout the follow-up period. Conclusions This re-port preliminarily demonstrated the feasibility and effectiveness of two-person collaborative repositioning approach in elderly patients with PD catheter displacement. Although the results have potential application value, further studies are needed to verify their generality and long-term efficacy in larger samples.